Garbhagriha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The main deity presides in the form of a linga in the garbhagriha (sanctum sanctorum) of the Hazareshwar Temple. The Shiva linga (aniconic representation of Shiva) is adorned with hazar or hundreds of miniature lingas. As a living temple, it reverberates with daily rituals of worship and offerings.